2006
DOI: 10.1007/s00705-005-0712-9
|View full text |Cite
|
Sign up to set email alerts
|

Yellow leaf of sugarcane is caused by at least three different genotypes of sugarcane yellow leaf virus, one of which predominates on the Island of Réunion

Abstract: The genetic diversity of sugarcane yellow leaf virus (SCYLV) was analyzed with 43 virus isolates from Réunion Island and 17 isolates from world-wide locations. We attempted to amplify by reverse-transcription polymerase chain reaction (RT-PCR), clone, and sequence four different fragments covering 72% of the genome of these virus isolates. The number of amplified isolates and useful sequence information varied according to each fragment, whereas an amplicon was obtained with diagnostic primers for 59 out of 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
49
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 15 publications
2
49
1
Order By: Relevance
“…SCYLV-strains from different American countries were characterized by fingerprinting and partial sequence analysis and a Colombian strain was postulated as a founder strain of SCYLV (Moonan and Mirkov 2002). Later Abu Ahmad et al (2006Ahmad et al ( , 2007 compared 60 SCYLV-preparations from almost all sugarcane-growing countries (including Colombia) by diagnostic PCR-reactions or by partial sequencing. They grouped the virus into 2 major strains, one called REU which is found mainly in Reunion Island, the other BRA-PER, which is found in North and South America.…”
Section: Introductionmentioning
confidence: 99%
“…SCYLV-strains from different American countries were characterized by fingerprinting and partial sequence analysis and a Colombian strain was postulated as a founder strain of SCYLV (Moonan and Mirkov 2002). Later Abu Ahmad et al (2006Ahmad et al ( , 2007 compared 60 SCYLV-preparations from almost all sugarcane-growing countries (including Colombia) by diagnostic PCR-reactions or by partial sequencing. They grouped the virus into 2 major strains, one called REU which is found mainly in Reunion Island, the other BRA-PER, which is found in North and South America.…”
Section: Introductionmentioning
confidence: 99%
“…Sequence analyses of the SCYLV genome revealed that some regions of SCYLV genome are closely related to Barley yellow dwarf virus (BYDV) and others that are similar to PLRV. It has been reported that the genetic diversity of SCYLV evolved through recombination between luteoviral and poleroviral ancestors (Abu Ahmad et al 2006;Moonan and Mirkov 2002;Smith et al 2000). The SCYLV genome consists of positive single-stranded genomic RNA (?ssgRNA), presented as a whole genome (*6 kb) with six recognized open reading frames (ORFs) that are expressed by a variety of mechanisms (Moonan and Mirkov 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The deduced amino acid sequence of P0 proteins is highly conserved among different geographic isolates of SCYLV (Abu Ahmad et al 2006;ElSayed et al 2011). However, the amino acid sequence identity between the P0s of poleroviruses is very low.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occurrence of five different genotypes of SCYLV has been reported (Abu Ahmad et al 2006a; Moonan and Mirkov 2002;Viswanathan et al 2008), and three of these genotypes have been found in Guadeloupe (Abu Ahmad et al 2006b). Variation in pathogenicity among some of these genotypes has also been reported (Abu Ahmad et al 2007).…”
Section: Introductionmentioning
confidence: 99%